2018
DOI: 10.1016/j.indmarman.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The varying roles of governance mechanisms on ex-post transaction costs and relationship commitment in buyer-supplier relationships

Abstract: This is a repository copy of The varying roles of governance mechanisms on ex-post transaction costs and relationship commitment in buyer-supplier relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 80 publications
(259 reference statements)
5
86
0
Order By: Relevance
“…Predominantly, such mechanisms were designed to reduce opportunistic behaviours of exchange parties mainly through contractual governance and legal-legitimate power (Lumineau and Henderson, 2012). However, the advancement of governance theory suggested that the role of governance mechanisms is also crucial in mitigating conflict and promoting cooperation between supply chain members (Cao and Lumineau, 2015;Shahzad et al, 2018), fostering information and knowledge sharing, improving supply chain agility, flexibility, financial and non-financial performance, as well as cultivating environmental sustainability ( Williamson, 1985;Poppo and Zenger, 2002;Inkpen and Tsang, 2005;Blome et al, 2013;Wacker et al, 2016;Um and Kim, 2018).…”
Section: The Role Of Governance Mechanisms In Supply Chain Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Predominantly, such mechanisms were designed to reduce opportunistic behaviours of exchange parties mainly through contractual governance and legal-legitimate power (Lumineau and Henderson, 2012). However, the advancement of governance theory suggested that the role of governance mechanisms is also crucial in mitigating conflict and promoting cooperation between supply chain members (Cao and Lumineau, 2015;Shahzad et al, 2018), fostering information and knowledge sharing, improving supply chain agility, flexibility, financial and non-financial performance, as well as cultivating environmental sustainability ( Williamson, 1985;Poppo and Zenger, 2002;Inkpen and Tsang, 2005;Blome et al, 2013;Wacker et al, 2016;Um and Kim, 2018).…”
Section: The Role Of Governance Mechanisms In Supply Chain Contextmentioning
confidence: 99%
“…Several informal instruments have been considered and examined in relation to relational governance such as trust (Nooteboom et al, 1997;Poppo and Zenger, 2002;Yu et al, 2006;Ghosh and Fedorowicz, 2008;Liu et al, 2017;Shahzad et al, 2018), communication and information exchange (Poppo and Zenger, 2002;Cao and Zhang, 2011;Bstieler and Hemmert, 2015), as well as collaboration (Cai et al, 2009;Hernández-Espallardo et al, 2013;Dong et al, 2017) between buying firms and suppliers. However, trust is regarded as the most prominent relational governance mechanisms compared to the others as it is deemed to have a significant role in improving supply chain performance (Poppo and Zenger, 2002;Ghosh and Fedorowicz, 2008;Burkert et al, 2012;Cao and Lumineau, 2015;Liu et al, 2017).…”
Section: Suppliers' Trust and Relational Governancementioning
confidence: 99%
See 1 more Smart Citation
“…Digital innovation management including these disruptive technologies does not only contribute to automation and optimization of the processes (increasing the efficiency by 15-20%) but also provide value-producing opportunities and profitability (20% of revenue generation) by reducing transaction costs [14] and minimizing errors [1]. Technological applications however are not enough for innovation excellence as several incumbent firms are ill prepared; it necessitates transformation to business model innovation [15], based on digital technologies such as blockchain.…”
Section: Significance Of the Research In Relation To Current Knowledgementioning
confidence: 99%
“…Recently, supplier relationship management (SRM, hereafter) has become a vital tool for achieving sustainable competitive advantage because of proliferating levels of outsourcing surfacing within global supply chains, growing supply uncertainties, diverse customer requirements as well as demand uncertainties that companies face in the competitive environment (Amoako-Gyampah et al , 2019; Zhang and Cao, 2018). Many companies have therefore sought to build strategic relationships with suppliers through supply chain relationships (Shahzad et al , 2018; Kim and Chai, 2017). A firm’s ability to have a comprehensive understanding of the buyer–supplier relationship is very important to the organization’s competitiveness (Munyimi and Chari, 2018).…”
Section: Introductionmentioning
confidence: 99%